MANAGEMENT OF INCLUSION PAUD CLASS AT CAHAYA KAUTSAR INCLUSION ISLAMIC KINDERGARTEN, EAST JAKARTA - Erlin Yusnita, SST.FT; Dian Farista, S. Pd.; Diana Indah Palupi, S.Pd; Emma Rahmani, S. P; Lilis Amperawati, S.IP; Rustatik,S.Pd.I (Universitas Panca Sakti Bekasi, 2023)
The education service system which requires that all children with special needs be served at the nearest Early Childhood Education (PAUD) institutions, in regular classes together with normal children of the same age is called inclusive education. Most people still view children with special needs as a disgrace and even become something that is frightening and embarrassing for some parents who have these children. They do not yet realize that these children are children who have potential that is immeasurable and resides in every child. The implementation of the inclusive school program in PAUD is currently still not optimal, this is due to the lack of readiness of schools to implement an inclusion system. One of them is the management or arrangement of classes in inclusive schools that have not fully accommodated the needs of children, especially children with special needs. For this reason, this study aims to determine classroom management in Cahaya Kautsar Islamic Inclusion Kindergarten, East Jakarta. The research was conducted in April 2023 using a qualitative descriptive method using data collection techniques, namely observation, interviews, and documentation. The results showed that the management of the inclusive class was carried out every day according to the distribution. Suppose there is a change situation or class division outside of what has been scheduled. In that case, it can be adequately resolved because communication and coordination between class teachers, accompanying teachers, and therapists are going well.